In vitro extracellular and intracellular activities of clavulanic acid and those of piperacillin and ceftriaxone alone and in combination with tazobactam against clinical isolates of Legionella species. - Edelstein, P H (1994)
The activities of ceftriaxone, piperacillin, tazobactam, clavulanic acid, and combinations of ceftriaxone or piperacillin with tazobactam against 22 clinical Legionella isolates were measured by broth microdilution and macrodilution methods and in macrophages. The broth microdilution MICs that inhibited 90% of strains tested were 2 and 1 microgram/ml for ceftriaxone and tazobactam, respectively. Broth macrodilution MICs were 8 and 1 microgram/ml, respectively, for the two Legionella pneumophila strains tested with piperacillin and were 0.25 and 0.5 microgram/ml, respectively, for clavulanate. No significant intracellular anti-L. pneumophila activity was observed for ceftriaxone (32 micrograms/ml), piperacillin (32 micrograms/ml), tazobactam alone (16 micrograms/ml), clavulanate alone (2 micrograms/ml), or tazobactam in combination with ceftriaxone (ceftriaxone/tazobactam at 32/4 and 16/16 micrograms/ml) or piperacillin (32/4 micrograms/ml). Erythromycin (1 microgram/ml) was active against intracellular L. pneumophila in the same macrophage model of infection. It is very unlikely that tazobactam or clavulanate, alone or in combination with beta-lactam antimicrobial agents, will be effective for the treatment of Legionnaires' disease in humans.